2013
DOI: 10.1007/s11547-013-0360-1
|View full text |Cite
|
Sign up to set email alerts
|

Trans-thoracic biopsy of lung lesions: FNAB or CNB? Our experience and review of the literature

Abstract: FNAB under CT guidance is subject to a lower rate of complications and, if performed in the presence of the pathologist, has a greater diagnostic accuracy compared to CNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 30 publications
5
44
1
Order By: Relevance
“…The present retrospective study of 155 patients demonstrated that CT-guided percutaneous lung biopsy of intrapulmonary solitary nodules of ≤30 mm in diameter had a high accuracy rate (90.3%), which is consistent with the findings reported by Lee et al (4), Hwang et al (9), Choi et al (15), Li et al (21) and Capalbo et al (22). Preoperative evaluation of puncture routes, preoperative guidance to properly control respiratory amplitude and frequency, avoidance of injury to major vessels and precise recognition of the tip position of the needle may help to maintain an acceptable risk/benefit ratio of the CT-guided biopsy, particularly for the examination of nodules close to major vessels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present retrospective study of 155 patients demonstrated that CT-guided percutaneous lung biopsy of intrapulmonary solitary nodules of ≤30 mm in diameter had a high accuracy rate (90.3%), which is consistent with the findings reported by Lee et al (4), Hwang et al (9), Choi et al (15), Li et al (21) and Capalbo et al (22). Preoperative evaluation of puncture routes, preoperative guidance to properly control respiratory amplitude and frequency, avoidance of injury to major vessels and precise recognition of the tip position of the needle may help to maintain an acceptable risk/benefit ratio of the CT-guided biopsy, particularly for the examination of nodules close to major vessels.…”
Section: Discussionsupporting
confidence: 92%
“…Rates of hemorrhage or hemoptysis have varied in previous studies; with values reported to be 4 (17), 9 (22), 14.5 (15), 20-22 (2) and 27% (13,23). Similar to Capalbo et al (22) and Choi et al (15), bleeding occurred in 10% of patients in the present study; patients with nodules of 21-30 mm had a significantly higher risk of hemorrhage compared with those with smaller nodules. Elevated bleeding risk may be associated with a rich blood supply in larger nodules.…”
Section: ------------------------------------------------------------supporting
confidence: 72%
See 1 more Smart Citation
“…As PLR >10 and NLR <0.1 are considered convincing evidence to rule in or rule out diagnoses, both PCNB and PNAB can effectively detect malignant lesions in the lung and PCNB is more advantageous than PNAB. Emanuela et al 34 indicated that PNAB carried out by a pathologist on site has a lower rate of complications and a higher diagnostic accuracy than PCNB in pulmonary lesions; however, at some centres, welltrained cytopathologists are not available to immediately interpret FNA specimens. In the publications included in the present analysis, the presence of a pathologist on site was not noted by any of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Charig and Phillips reported similar accuracy of FNAB and core biopsy when an on-site pathologist was available; in a similar setting Capalbo et al observed a greater diagnostic accuracy of FNAB compared to core needle biopsy (94.83% vs. 81.82. %) [36]. Nowadays, the test of genetic mutations is important to plan targeted therapies in patient with lung cancers.…”
Section: Diagnostic Accuracymentioning
confidence: 99%